KONTAMINASI MERKURI DALAM SEDIMEN DI SUNGAI TALAWAAN - Komalig, Rino (CHEMISTRY PROGRESS, 2010)
ABSTRACTKomalig et al., 2010. Mercury contamination within Talawaan river sediment.Sediment plays an important role in controlling concentrations of heavy metals which accumulate in body tissues aquatic biota. Contamination of mercury in river sediments due to natural processes (weathering of mineralized rocks), the traditional processing of gold (amalgamation), or industrial processes that use raw materials containing mercury.This research is descriptive analytical that is describing the Hg content in the sediment. Sample preparation is done by following the instructions of JPHA, followed by analysis of sediment samples using AAS-CV. Then using Anova test to see the relationship of Hg distribution in the river from the mine based on the distance.Results showed that total Hg in sediment Hg concentrations found differences based on distance, where the farther from the mine, the smaller the concentration of Hg.Keywords : sediment, heavy metals, Hg, river